The benefits and risks of using river sediment for agriculture : a case study of the Nhieu Loc canal in Ho Chi Minh city, Vietnam - Nguyen Thi Kim Phuong; Preeda Pakpian; Nguyen, Thi Kim Oanh; Fukushi, Kensuke; Danish International Development Assistance (Danida) (Bangkok : Asian Institute of Technology, 2001)
Application of river sediment on agricultural land as an alternative for crop fertilizers is now receiving more public attention. This is because most of river sediments usually contain not only certain levels of plant nutrients but also significant quantity of trace elements including toxic heavy metals. Those heavy metals might have pose some hazards or risk to human life and the environment as when such sediments being used at high dose continuously for a longer time. As a result, toxic elements distribute and accumulate in the soil as well as uptaken by the cops and reach the animals and human beings. The overall objectives of this research include characterized compositions of a sediment obtained from Nhieuloc canal, asses its potential use in terms of heavy metal contamination on soil and crop grown as well as crop yield. Potential health risk by consumption of the crop was put forward for investigation. Mobility, bioavailability and concentrations of heavy metals containing in the sediment were evaluated with the use of chemical extraction techniques such as DTP A and sequential extraction. DTP A was selected to use as a single extractant for evaluation of bioavailability of heavy metals in sediment whereas sequential extraction was used to partition the heavy metals in sediment into six different defined phases ranging from most solubilized to least solubilizedbased on its geochemical linkage forms: Exchangeable, carbonate, easily reducible, moderately reducible, organic and residual phase. Further the sum of metals in exchangeable and carbonate fractions obtained from sequential extraction scheme was used to evaluate the potential plant available. Cabbage field experiment applied with different rates of sediment (:::::: 28 and 42 ton/ha or equivalent to 1 OOkgN/ha and 150kgN/ha) were conducted in comparison with chemical fertilizer at the similar N rates. Results show that both plant available and total heavy metal concentration were found higher in those plots treated with higher loading rates of sediment (42 ton/ha). The concentrations of heavy metals (Cu, Zn, Pb) in soil were decreased with time after crop harvesting and the residues remain in the soil were well below those of the UK, USA and Germany standards. Concentration of Zn, Cu, Pb, Cd and Ni was detected in the cabbage tissue. The upper concentration of these metals includes Zn at 131.53 mg/kg, Cu at 20.84 mg/kg, Pb at 0.06 mg/kg, Cd at 0.21 mg/kg and Ni at 0.44 mg/kg dry matter. None of these metals concentration exceeded the tolerable limits of plant. Further appreciable amount of heavy metals accumulation on cabbage tissue is not significant higher from dietary weekly intake allowed. The application of the river sediment to agricultural land exhibited positive response to the plant growth. The effect of sediment was found statistically insignificant with respect to heavy metals accumulation in plant tissues. Nhieuloc sediment is therefore regarded as safe and beneficial to agricultural reuse in this region. In order to safeguard the health of consumers and environment monitoring of soil heavy metal build up both in the plough layer (O-l 5cm) and in deeper layers avoiding metal leachability to contaminate groundwater shall be conducted in every 3-5 year plan if the sediment is extensively used at a high loading rate (20 - 50 ton/ha/year). l
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2001
Keywords: River sediments -- Vietnam -- Ho Chi Minh; Agriculture -- Vietnam -- Ho Chi Minh